Metafunction Analysis of the Jordanian Curriculum Action Pack-12 Reading Materials to Improve English Language Learning and Teaching in Public Schools - Slim, Suha Abdul Razzaq (Journal of Educational and Psychological Sciences, 2022)
This study aims at examining the effect of utilizing the metafunction meanings in teaching Action Pack 12 reading materials of the second semester of the year 2021 on improving Twelfth grade learners’ reading abilities and to determine to what extent the Action Pack 12 reading materials promote the accurate communication skills among Jordanian learners based on the metafunction meaning as part of the SFL. study investigated whether the use of the metafunction meaning available in the reading materials enhance Twelfth grade learners with better understanding of reading materials that would integrate in improving other language skills as well. Therefore, a qualitative research methodology was carried out to examine the extent in which the reading materials comprise metafunction meaning tasks improving learners’ comprehensive reading abilities and communicative skills in English. The findings of the analysis of the study revealed that all the reading materials of Action Pack twelve include metafunction meanings activities and tasks within the three types of meanings which are the ideational, interpersonal and textual meanings varying in their levels’ of difficulty and genres. This tendency to include metafunction meanings in all the reading materials ensures the effectiveness of developing learners’ readings skills and communicative skills to employ the English language in authentic contexts meaningfully in the outer world.